(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to determine how the tourist attraction, amenities, accessibility, supporting facilities and institutional policies for tourism development in the Malino area, Gowa Regency. This study used descriptive qualitative research. The number of informants in this study was 8 people. Data collection techniques were observation, interviews, and documentation. The results of the study showed that aspects (1) tourism had been running, but the existence of Covid, the tourism development policy activities had not been maximized and were hampered by the allocation of funds. (2) The accessibility of each tourism development policy was less visible from the many roads that were potholes, narrow, but this was of course a special concern for local governments. (3) The amenities in tourism development policies were already running well. This could be seen in terms of the number of facilities provided by the government. (4) The supporting facilities for tourism development policies were good. This could be seen in terms of the infrastructure provided. (5) The tourism development policy institutions were already running well. This could be seen from the existence of an activity called Beautiful Malino, all people and business owners were involved Keywords: Policy, tourism development